2020
DOI: 10.1111/ssqu.12859
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of Cultural Theory Survey Measures

Abstract: Objective. Cultural Theory (CT) has attracted significant attention across the social sciences and is increasingly being used in survey research. We assess the construct validity of three CT survey operationalizations to help interpret and improve these measures. Methods. A coding protocol for face and content validity of survey items was developed with input from several CT scholars and applied independently by two of authors of this article. Convergent, discriminant, and predictive validity of these items we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 75 publications
(116 reference statements)
1
23
1
Order By: Relevance
“…To measure the worldviews associated with cultural theory, I draw on a set of questions used in several previous cultural theory studies (see Bundrick & Nowlin, 2020; Jackson, 2015; Jones, 2011; Moyer & Song, 2019; Nowlin & Rabovsky, 2020; Ripberger et al, 2012; Tumlison & Song, 2019). Additionally, a recent analysis of the cultural theory questions used found that they lack face and content validly; however, they possesses convergent, discriminant, and predictive validity (Swedlow et al, 2020). Respondents were asked their agreement, on a 1 (strongly disagree) to 7 (strongly agree) scale, with three statements, presented in random order, for each cultural type.…”
Section: Data and Variablesmentioning
confidence: 99%
“…To measure the worldviews associated with cultural theory, I draw on a set of questions used in several previous cultural theory studies (see Bundrick & Nowlin, 2020; Jackson, 2015; Jones, 2011; Moyer & Song, 2019; Nowlin & Rabovsky, 2020; Ripberger et al, 2012; Tumlison & Song, 2019). Additionally, a recent analysis of the cultural theory questions used found that they lack face and content validly; however, they possesses convergent, discriminant, and predictive validity (Swedlow et al, 2020). Respondents were asked their agreement, on a 1 (strongly disagree) to 7 (strongly agree) scale, with three statements, presented in random order, for each cultural type.…”
Section: Data and Variablesmentioning
confidence: 99%
“…CT was originally developed to explain cultural differences in the perception of risks (Douglas, 1970, 1992). Since then, it has been used to examine controversial issues related to nature and other social phenomena (Gerlach and Rayner, 1988; Johnson and Swedlow, 2021; McNeeley and Lazrus, 2014; Ney and Thompson, 2000; Simmons, 2018; Slovic and Peters, 1998; Swedlow et al, 2020).…”
Section: The Narrative Policy Framework: Situating Our Studymentioning
confidence: 99%
“…Egalitarianism: What society needs is a fairness revolution to make the distribution of goods more equal. Furthermore, Swedlow et al (2020Swedlow et al ( , p. 2332 show that even approximate measures of cultural dimensions can be used to predict attitudes and behaviors that CT hypothesizes.…”
Section: Fundingmentioning
confidence: 99%